Pengukuran Kapasitas Vo₂Max Atlet Handball di Kota Makassar Menggunakan Bleep Test - Andi Fatwa Nauval; Roswanda Saputri; Friska Enytama El Husna; Alif Kurniawan; Haerul Ma’ruf; Irvan; Poppy Elisano Arfanda (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Cardiovascular endurance is an important component of physical fitness in handball, a sport that demands repeated high-intensity activity. This ability is related to the body's capacity to supply oxygen to muscles during physical activity and can be measured through VO₂Max values. This study aims to determine the level of cardiovascular endurance of handball athletes in Makassar City. The study used a quantitative descriptive method with a population of all handball athletes in Makassar City. The study sample consisted of 16 athletes determined using a saturated sampling technique. Data collection was carried out through a cardiovascular endurance test using the Multi Stage Fitness Test (Bleep Test) to obtain the athletes' VO₂Max values. Data were analyzed using descriptive statistics to group the athletes' cardiovascular endurance levels into certain categories. The results showed that the average VO₂Max value of handball athletes in Makassar City was in the low category. This finding indicates that the athletes' cardiovascular endurance is not optimal. The implication of this study is the need for planning and implementing a more systematic, structured, and sustainable physical training program to improve cardiovascular endurance and support the improvement of handball athletes' performance.